Hospital-based cross-sectional study on the clinical characteristics of children with severe acute respiratory infections in Hungary - Nikolett Orosz; Gabriella Gömöri; Ulambayar Battamir; Attila Csaba Nagy (BMC Infectious Diseases)
Abstract Background Severe acute respiratory infection (SARI) is a major cause for hospital admission and associated with high mortality among children worldwide. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza viruses and respiratory syncytial virus (RSV) are the most frequently identified pathogens in children with SARI. The duration of care can be affected by the type of infection and patient characteristics. Therefore, the objective of this study was to identify factors affecting the length of hospitalization in children infected with SARS-CoV-2, influenza A and RSV. Methods We collected data on 713 children with SARI from the medical databases of a university hospital in Hungary. To examine whether there is a difference in the length of hospitalization in children with the SARI Kruskal-Wallis test was performed. To determine the factors that may have an impact on the duration of care a multiple logistic regression analysis was executed. Results Our results showed that among RSV infected patients the proportions of children requiring intensive care (8.94%), mechanical ventilation (8.94%) and oxygen therapy (13.01%) and suffering from pneumonia (29.27%) were larger than among cases with SARS-CoV-2 and influenza A infection. Considering the age distribution and the duration of care in children with SARI, cases with RSV were significantly younger (p < 0.001) and stayed longer in the hospital (median: 5 days, IQR: 4–7 days, p < 0.001) than those with SARS-CoV-2 and influenza A virus. Multiple logistic regression analysis showed that RSV infection (adjusted odds ratio (aOR): 3.25, 95% confidence interval (CI): 1.43–7.38; p = 0.005), pneumonia (aOR: 3.65, 95% CI: 2.14–6.24; p < 0.001), mechanical ventilation or oxygen therapy (aOR: 3.23, 95% CI: 1.29–8.11; p = 0.012) and underlying illnesses (aOR: 2.39, 95% CI: 1.35–4.23; p = 0.003) significantly increased the odds of hospitalization for more than 4 days. Conclusions Our research showed that of the viruses causing SARI, RSV had the greatest clinical relevance, contributing to hospital stays of more than 4 days in a large share of paediatric patients below 1 year of age. Our results supply new information on children with SARI, and provide evidence for health policy makers to allocate additional resources to hospitals during SARI epidemics.